2000
DOI: 10.1080/080352500750028195
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of nebulized surfactant therapy for neonatal respiratory distress syndrome

Abstract: Thirty-four spontaneously breathing newborns with respiratory distress syndrome (RDS) requiring nasal continuous positive airway pressure (CPAP) and an arterial-to-alveolar oxygen tension ratio (a/A PO2) of 0.15-0.22 were randomized to treatment with nebulized surfactant (Curosurf) or to serve as controls. All children were first supported by nasal CPAP according to normal clinical routines. Surfactant was administered using a modified Aiolos nebulizer, and a total of 480 mg was aerosolized in each case. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
96
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 21 publications
0
96
0
1
Order By: Relevance
“…1,2 Tracheal instillation requires an endotracheal tube to be placed; hence surfactant is usually administered at initiation of or during mechanical ventilation (MV). However, MV in itself may induce varying degrees of lung injury, with epithelial disruption followed by fluid leakage and inflammatory response that can inactivate surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Tracheal instillation requires an endotracheal tube to be placed; hence surfactant is usually administered at initiation of or during mechanical ventilation (MV). However, MV in itself may induce varying degrees of lung injury, with epithelial disruption followed by fluid leakage and inflammatory response that can inactivate surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Valls-i-Soler and colleagues showed that use of a dual lumen tube rather than disconnection from the ventilator led to fewer dosing problems. 47 To date, it has not been possible to demonstrate that surfactant can be successfully administered by nebulization, 48 although this remains an attractive route as it avoids intubation of the trachea. Four methods of administration that aim to reduce the duration of endotracheal intubation or avoid it altogether have been described.…”
mentioning
confidence: 99%
“…Until now, there have been four clinical studies on nebulized surfactant as rescue therapy (13)(14)(15)(16). These studies confirmed the safety and feasibility of the method.…”
mentioning
confidence: 51%